Factors Affecting Customer's Intention Towards Purchasing Halal Collagen Beauty Drinks In Malaysia: A Structural Equation Modelling - Siti Nazirah Omar; Siti Radhiah Omar; Siti Nurul Aini Mohd Rodzi; Nurul Azlinda Chek Talib; Nor Hamiza Mohd Noor (Universiti Malaysia Kelantan (UMK), 2024)
Volume 7 Issue 2